Migration and the rural-urban continuum: evidence from the rural Philippines - Quisumbing, Agnes R.; McNiven, Scott (International Food Policy Research Institute, 2005)
This paper explores the diversity of the experience of migrants to rural, peri–urban, and urban areas using a unique longitudinal data set from the Philippines. In 2003 and 2004, the Bukidnon Panel Study followed up with 448 families in rural Mindanao who were previously interviewed in 1984/85 by the International Food Policy Research Institute and the Research Institute for Mindanao Culture, Xavier University, and surveyed both a sample of their offspring living in the same area as well as a sample of those who had moved away to different locations. Parents (original respondents) and children who formed separate households in the same locality were interviewed in 2003; original respondents’ offspring that migrated to different rural and urban areas were interviewed in 2004. Thus, migration patterns were examined using the full listing of children of the original respondents as well as a special survey of 257 of their migrant offspring who were tracked down in 2004. This migrant survey focused on differences in the migration experience of males and females who moved to other rural areas, poblaciones (the administrative seats of municipalities or towns), and urban areas. We follow this with an examination of the determinants of children’s location, using the sample of all children. In addition to migration to rural, peri–urban, and urban destinations, we explicitly consider the case where the individual leaves his or her parental residence, but remains in the same village, as a locational choice.